Regional anatomy: musculature of the neck - van Schoor, Albert (Henry Stewart Talks, 2022)
Organization of the neck, Superficial muscles of the neck, Triangles of the neck, Muscles of the anterior cervical region, Suprahyoid muscles, Infrahyoid muscles, Prevertebral muscles, Muscles of the cervical viscera